Micro and meso-level issues affecting potato production and marketing in the tropical highlands of Sub-Saharan Africa: The known and the unknowns - Okello, J.J.; Kwikiriza, N.; Kakuhenzire, R.; Parker, M.; Schulte-Geldermann, Elmar; Pambo, K.O. (2015)
This study uses ecological system theory to examine the micro and meso level factors that affect and are affected potato production in Sub-Sahara Africa. It focuses on gender, environmental factors, food security. The data and information used were collected using both qualitative and quantitative methods. The study finds that gender use within the households is changing. It also finds that dwindling land sizes and soil fertility are encouraging the migration potato plots to fragile margins while increased pest and disease pressure is encouraging greater reliance on pesticide -- resulting into increased incidences of pesticide poisoning, all of which have definite effects on the environment and sustainability of potato production and agriculture in general. It concludes that farm household (micro-level) decisions on potato production are driving and being driven by the environmental/ physical (meso) level ecology. The study discusses the implications of its findings for policy and sustainability of agriculture